The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4103/ijnmr.ijnmr_79_17
|View full text |Cite
|
Sign up to set email alerts
|

Improving nursing students' learning outcomes in fundamentals of nursing course through combination of traditional and e-learning methods

Abstract: Background:Fundamentals of nursing course are prerequisite to providing comprehensive nursing care. Despite development of technology on nursing education, effectiveness of using e-learning methods in fundamentals of nursing course is unclear in clinical skills laboratory for nursing students. The aim of this study was to compare the effect of blended learning (combining e-learning with traditional learning methods) with traditional learning alone on nursing students' scores.Materials and Methods:A two-group p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 29 publications
3
28
0
2
Order By: Relevance
“…On the other hand, there remains a need for more research to clarify a number of questions about the effectiveness of education conducted through e-learning. 20 During the COVID-19 pandemic, individuals' daily routines have changed considerably and they have been more likely to remain at home. Some individuals have developed strategies for engaging in online activities such as virtual gaming, increased use of social media, and increased use of online shopping to reduce their levels of anxiety and stress.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there remains a need for more research to clarify a number of questions about the effectiveness of education conducted through e-learning. 20 During the COVID-19 pandemic, individuals' daily routines have changed considerably and they have been more likely to remain at home. Some individuals have developed strategies for engaging in online activities such as virtual gaming, increased use of social media, and increased use of online shopping to reduce their levels of anxiety and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Nesta metodologia o aluno Ă© o centro e, portanto, participa ativamente. O contexto atual de ensino e trabalho em que estamos inseridos, exige o desenvolvimento de novos comportamentos diante das novas tecnologias, o que cinge ao professor entender a nova geração de alunos, uma vez que essa nova geração se desenvolveu numa Ă©poca de grandes avanços tecnolĂłgicos e prosperidade econĂŽmica conforme compreende Sheikhaboumasoudi et al (2018).…”
Section: Discussionunclassified
“…E-learning has been shown to have a positive impact on the achievement of learning outcomes in health professions education. A recent study found that a mixed methods approach that combined traditional learning activities with e-learning improved clinical skills in nurses [9]. Another study examining the impact of e-learning on achievement of learning outcomes in a medical immunology course found that on average 3.6% of the class performed better on the immunology component of the examination, which was linked to the level of engagement with the online material [10].…”
Section: Discussionmentioning
confidence: 99%